Implementasi TOPSIS (Technique For Order Preference By Similarity To Ideal Solution) Untuk Penentuan Tempat Pembuangan Akhir - Rachmat Agung Pambudi; Agung B Prasetijo; Yudi E Windarto (Universitas PGRI Semarang, 2019)
Human population produces a fairly high waste every year. In Pemalang District there is only one final disposal site which is at Pegongsoran Village. A decision support system is needed that is expected to provide alternative options for determining the best landfill location other than such a site. In selecting the location of the Final Disposal Site, a method that can process data from each available alternative is needed. (TOPSIS) Technique For Order Preference By Similarity To Ideal Solution is one of the various Decision Support System methods. TOPSIS is a multi-criteria method for identifying limited alternative sets based on minimizing the distance of the farthest ideal point and maximizing the distance of the lowest ideal point. Based on the calculation using the TOPSIS method, the available data is fourteen districts as an alternative location choice and seven parameters have been found that Warungpring District has the highest rank and Pulosari District has the lowest rank. Then the results of these calculations will be visualized using Carto Map on an information system.